VD_FINDINFO Décision / 2013 / 402 vom 22. März 2013 - VD Tribunal cantonal (2013)
RÉVOCATIONEN GÉNÉRAL, AVOCAT D'OFFICE, CHOIX DE L'AVOCAT, DÉFENSE D'OFFICE | 133 CPP (CH), 134 CPP (CH), 393 al. 1 let. a CPP (CH)